Money Growth and Aggregate Stock Returns - Tobias Böing; Georg Stadtmann (Credit and Capital Markets – Kredit und Kapital, 2017)
We empirically evaluate the predictive power of money growth measured by M2 for stock returns of the S&P 500 index. We use monthly US data and predict multiperiod returns over 1, 3, and 5 years with long-horizon regressions. In-sample regressions show that money growth is useful for predicting returns. Higher recent money growth has a significantly negative effect on subsequent returns of the S&P 500. An out-of-sample analysis shows that a simple model with money growth as a single predictor performs as goods as the constant expected returns model, while models with several predictor variables perform worse than those simple models. – – Geldmengenwachstum und Aktienmarktrenditen In diesem Artikel wird die Vorhersagekraft des Geldmengenwachstums, welches mit dem Geldmengenaggregat M2 gemessen wird, für die Aktienrenditen des S&P 500 Indices gemessen. Wir verwenden Monatsdaten der USA und prognostizieren Mehrperiodenrenditen über 1, 3 und 5 Jahre mit Regressionsmodellen. Die Ergebnisse im gesamten Schätzzeitraum zeigen, dass das Geldmengenwachstum Aktienrenditen prognostizieren kann. Demnach sind bei einem hohen Geldmengenwachstum geringere Aktienrenditen in den Folgejahren zu erwarten. Die Out-of-Sample-Analyse zeigt, dass die Prognosen eines Modells mit Geldmengenwachstum als einziger Prädiktor etwa so gut abschneidet wie das Modell mit konstanten erwarteten Renditen. Die komplexeren Modelle mit mehreren Prädiktoren zeigen in der Out-of-Sample-Analyse dagegen eine schlechte Prognosefähigkeit.
Keywords: M2; G14; G17; C58; E44; E47; 330; Out-of-Sample; Money growth; Stock Market; S&P 500; Stock Returns